Pengembangan Lanjut Aplikasi Supervisi Pembelajaran berbasis Mobile (LESON) - Febrian Diaz Maulana; Ratih Kartika Dewi; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The quality of human life will develop along with the development of technology. The results of the application of technology indicate an increase in the quality of life in the field of education such as the emergence of applications for mobile devices that have an impact on teachers in the field of education, such as when supervising learning. The application of technology by taking photo and or video documentation takes place separately, but this causes the need for more efforts to compile data on the results of activities. This encourages the authors to develop applications for mobile devices as a solution. Application development uses the scrum software development method with iterative characteristics. The stages of application development include a requirements analysis consisting of a general description of the system, identification of actors, numbering rules, a list of functional requirements, a list of functional requirements specifications, a list of non-functional requirements, and requirements modeling; then design and implementation which consists of designing sequence diagrams, class diagrams, database design and implementation, program code, and interfaces. The results of application development are application artifacts for mobile devices that have gone through four tests, namely blackbox with valid results for all functional requirements, portability with valid results for three functional requirements on three system versions, compatibility with valid results for three interfaces on three screen versions, and usability with feedback from three users.